INTEGRATION OF LOCAL WISDOM VALUES OF LUBUK LARANGAN IN CIVIC EDUCATION LEARNING - zhafira oktafiani lukitosari Lukitosari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This article aims to analyze the potential integration of local wisdom values of Lubuk Larangan in Citizenship Education (PKn) learning. As a tradition of community-based resource management, Lubuk Larangan reflects various educational values, including mutual cooperation, social solidarity, ecological awareness, compliance with customary norms, and social justice. The study used a literature review method to analyze the relevance of Lubuk Laranganvalues to the concept of ecological citizenship, local wisdom-based learning, and the principles of Pancasila. The results of the analysis show that Lubuk Larangan can be a real example in building student character education, strengthening the relevance of PKn learning to the local context, and supporting the achievement of the Pancasila Student Profile dimensions. The integration of Lubuk Larangan in PKn learning can be done through a contextual, project, and value-based approach, which allows students to develop critical thinking skills, collaboration, and environmental awareness. In addition, this tradition can be used as a means to strengthen legal awareness and students' understanding of the importance of environmental sustainability. By presenting local wisdom of Lubuk Larangan in PKn learning, students not only gain conceptual understanding, but also real experience of the relationship between traditional values, customary law, and citizenship. This study recommends strengthening local wisdom-based curriculum, teacher training, and developing creative learning media to support this integration. These findings contribute to the literature on culture-based learning and the importance of strengthening citizenship education that is relevant to the local context.Keywords: local wisdom; ecological citizenship; educational values; customary norms; character education